Intellectual functionality of speech in children of older preschool age with logopathology - O.B. Bielova (Zaslavsky O.Yu., 2024)
Background. The purpose of this study is to identify the current state of intellectual functioning, which affects the speech readiness to study at school, of older preschool children with logopathology. The study included 607 older preschool children (5-6 years old), 250 with normotypical psychophysical development and 357 with speech disorders (dyslalia, stuttering, rhinolalia, dysarthria). Materials and methods. To evaluate the intellectual functioning of older preschool children with logopathology, methods were developed aimed at studying visual-motor coordination, auditory-verbal memory, verbal-spatial representation, verbal-logical thinking, verbal attention. Results. The results of the experimental study give a clear idea that there are significant differences in the formation of intellectual functionality between children with logopathology and those with normotypical psychophysical development. Older preschool children with speech disorders had low ability to copy graphic images, violations of independent control and planning their own activities, problems with the consistent reproduction of words, the volume of memorization, the strength of retention of stimuli, the speed and accuracy of reproduction of speech information, the difficulties understanding spatial relations in the addressed and own speech; verbal and logical skills are formed heterogeneously. Some preschoolers with logopathology can classify objects by features, generalize them, understand the figurative meaning of words and the content of texts. Others experience certain difficulties and make many mistakes; their verbal attention is not sufficiently developed, which prevents children from perceiving educational material. Conclusions. Accordingly, low indicators of visual-motor coordination, auditory-verbal memory, verbal-spatial representation, verbal-logical thinking, verbal attention in older preschool children with speech disorders indicate insufficiently formed intellectual functionality. This will affect their speaking readiness and learning the curriculum at school.